Optimisation of ultrasound-assisted extraction of phenolic antioxidants from Ilex guayusa Loes. leaves using response surface methodology. Issue 1 (January 2020) - Arteaga-Crespo, Yasiel; Radice, Matteo; Bravo-Sanchez, Luis Ramón; García-Quintana, Yudel; Scalvenzi, Laura
Abstract: The present study carried out the optimisation of the total polyphenol content (TPC) extraction assisted by ultrasound in Ilex guayusa leaves applying response surface methodology (RSM). Also, the evaluation of the antioxidant activity of the extract obtained under the optimal extraction conditions was performed. The effect of the variables like, time of sonication, temperature, ethanol/water ratio and solid/liquid relationship and the interactions between them were analysed through the use of a factorial design 2ˆ4. The significant factors were considered for the optimisation, employing a Box-Behnken Design, and the TPC as response variables. It was found that a quadratic model was adequate, with an adjusted R 2 value of 0.9367. The optimal conditions proposed, by the response surface model were: an extraction temperature of 60 °C, sonication time of 29.9 min and ethanol/water ratio of 76.8/23.2. The optimised leaves extract of I. guayusa show a TPC of 3.46 (±0.17) g gallic acid equivalents/100 g d.w. Radical scavenger activity of the obtained extract at optimum conditions, was performed through the FRAP and ABTS methods, given as result: 0.080 mmol TROLOX equivalents/100 g d.w. and 40.71 μmol TROLOX equivalents/g d.w., respectively. Due to the present findings, I. guayusa extracts can be proposed as a promising component for functional beverages, cosmetic and pharmaceutical formulation. Abstract : Engineering; Chemistry; Food science; Natural extracts; Natural antioxidants; Design expert; ABTS; FRAP.